In vitro bio-interaction responses and hemocompatibility of nano-based linear low-density polyethylene polymer embedded with heterogeneous TiO2/ZnO nanocomposites for biomedical applications. Issue 10 (3rd July 2021) - Harun, Nor Hazliana; Mydin, Rabiatul Basria S. M. N.; Sreekantan, Srimala; Saharuddin, Khairul Arifah; Seeni, Azman
Abstract: An innovative nano-base polymer that scavenges radicals and reactive oxygen species exhibits potential antibacterial properties, which are crucial in the biomedical field, particularly in reducing nosocomial infections. However, the safety of this nano-based polymer, which has direct contact with the human system, has not been fully understood. The present study investigated the cytocompatibility and hemocompatibility responses of linear low-density polyethylene polymer (LLDPE) embedded with difference ratios of heterogeneous TiO2 /ZnO nanocomposites. Exposure of the blood and fibroblast cells to LLDPE/100Z and LLDPE/25T75Z/10% nanocomposite films for 48 and 72 h decreased their viability by less than 40%, compared with LLDPE, LLDPE/100T and LLDPE/25T75Z/5% nanocomposite films. It also presented possible cellular damage and cytotoxicity, which was supported by the findings from the significant release of extracellular lactate dehydrogenase profiles and cell survival assay Further observation using an electron microscope revealed that LLDPE films with heterogeneous 25T75Z/5% promoted cell adhesion. Moreover, no hemolysis was detected in all ratios of heterogeneous TiO2 /ZnO nanocomposite in LLDPE film as it was less than 0.2%, suggesting that these materials were hemocompatible. This study on LLDPE film with heterogeneous TiO2 /ZnO nanocomposites demonstrated favorable biocompatible properties that were significant for advanced biomedical polymer application in a hospital setting.